(untitled) (EAAE Annual Conference Proceedings, 2023)
This paper is the result of multiple dialogues conducted among students and educators part of the Nordic Baltic Academy of Architecture. These conversations were initiated by three questions: What skills should students have after studying architecture? How should these skills be taught? How can architectural education be of special importance to our society?